The Effect of Transformational Leadership Towards Affective Commitment In Vocational Schoolof West Kalimantan - Ahmad Yani T; Rustam Rustam; Agus Syahrani; Sulha Sulha; Mahmuda Sumarno (JETL (Journal of Education, Teaching and Learning), 2024)
In the era of industrial revolution 4.0, the functional reformation must be conducted to vocational education. The vocational education sector has been in a crucial position to prepare good quality human resources (teachers and students) that are well-prepared in the era of industrial revolution 4.0. An ability of computer literacy and noble character (akhlakul karimah) of human resources are two essential aspects that have been concern in the effort of the superior human preparation. Therefore, this aim of this study is to develop a new model of affective commitment and see its impact to transformational leadership in vocational school across west Kalimantan. A quantitative approach using partial least squares path modeling (PLS-SEM) Wrappls version 7 was used to calculate 254 data sample from 29 private and public vocational high schools throughout West Kalimantan. The result revealed that the role of affective commitment as a mediating variable had been able to provide a positive and significant influence as well as this variable was able to improve the performance of leaders and teachers in vocational high schools throughout West Kalimantan through exogenous variables in the form of transformational leadership.